2021
DOI: 10.1186/s12967-021-03027-6
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine inhibits mitochondria damage and apoptosis of enteric glial cells in experimental intestinal ischemia/reperfusion injury via SIRT3-dependent PINK1/HDAC3/p53 pathway

Abstract: Background Intestinal ischemia/reperfusion (I/R) injury commonly occurs during perioperative periods, resulting in high morbidity and mortality on a global scale. Dexmedetomidine (Dex) is a selective α2-agonist that is frequently applied during perioperative periods for its analgesia effect; however, its ability to provide protection against intestinal I/R injury and underlying molecular mechanisms remain unclear. Methods To fill this gap, the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 76 publications
(72 reference statements)
0
23
0
Order By: Relevance
“…The antioxidant capacity of dexmedetomidine have been reported in some studies (33). A recent study reported that dexmedetomidine protects against oxidative injury through the regulation of oxidative stress via SIRT3 after intestinal ischemia reperfusion (34). In addition, several researches have reported that SIRT3 could regulate ROS generation mainly by changing the acetylation of SOD2, thereby controlling redox equilibrium (35,36).…”
Section: Discussionmentioning
confidence: 97%
“…The antioxidant capacity of dexmedetomidine have been reported in some studies (33). A recent study reported that dexmedetomidine protects against oxidative injury through the regulation of oxidative stress via SIRT3 after intestinal ischemia reperfusion (34). In addition, several researches have reported that SIRT3 could regulate ROS generation mainly by changing the acetylation of SOD2, thereby controlling redox equilibrium (35,36).…”
Section: Discussionmentioning
confidence: 97%
“…Consistently, Zhang et al ( 9 , 16 ) proved that DEX could protect against intestinal I/R-induced intestinal injury by suppressing apoptosis and inflammatory response of intestinal mucosal epithelial, preserving gut-vascular barrier impairment and subsequent liver damage. The other study indicated that pretreatment with DEX markedly attenuate the intestinal I/R injury, probably by enhancing mitophagy and reducing apoptosis of enteric glial cells ( 7 ). Moreover, DEX could inhibit hypoxia/reoxygenation-induced IEC ER stress, apoptosis, and pyroptosis via activating SIRT1 expression ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…DEX has been reported to be a potential drug for the prevention and treatment of intestinal I/R injury ( 7 , 9 , 16 , 18 , 19 ). Our results elaborated that the protection from DEX in mice with intestinal I/R injury evidenced with an inhibition of inflammation, ER stress-dependent apoptosis, and oxidative stress in the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The action mechanism of dexmedetomidine on mitochondria is strongly related to the SIRT family, which inhibits endoplasmic reticulum stress-induced pyroptosis in intestinal epithelial cells via SIRT1 expression ( 82 ). Moreover, the SIRT3-dependent regulation of the PINK1/HDAC3/p53 pathway can inhibit mitochondrial damage and apoptosis in enteric glial cells ( 83 ).…”
Section: Discussionmentioning
confidence: 99%